Effect of sono-osmodehydration pretreatment on the mass transfer kinetics, freezing characteristics and quality attributes of frozen carrot (Daucus carota) - Ghooshi, Fatemeh; Nourani, Moloud (International journal of refrigeration, 2024)
•Sono-osmodehydration was used to accelerate the freezing process.•A new exponential model was proposed for the prediction of WL and SG.•Dehydration pretreatment shortened the freezing time significantly.•High sonication duration resulted in structural damage, as confirmed by SEM.•Sono-osmodehydration at 40 % concentration-35 °C was the most favorable condition. Considerable efforts have been made to minimize the adverse effects of freezing on the quality of frozen products. In this study, ultrasound-assisted osmodehydrofreezing (UOD) was used to accelerate the freezing process. The effects of osmotic solution concentration, temperature, and application of ultrasound on freezing characteristics and quality attributes of frozen carrot were investigated. The changes in water loss (WL) and solid gain (SG) were predicted using kinetic models, with effective diffusivities determined according to Fick's second law of diffusion for a finite cylinder. The results from the kinetic modeling demonstrated the good fitness of the new proposed exponential model. Effective diffusivities for WL and SG ranged from 4.49 × 10−8 m2 s−1 to 8.42 × 10−8 m2 s−1 and 4.30 × 10−8 m2 s−1 to 5.12 × 10−8 m2 s−1, respectively, with the highest diffusivities observed in ultrasound-assisted dehydrated samples at 45 °C in a 60 % sucrose solution. Dehydration pretreatment could shorten the freezing time significantly. Pretreated samples (after thawing) showed higher firmness and lower phenolic contents, as compared to the control samples (freezing without osmodehydration). In addition, the UOD process minimized drip loss and electrolyte leakage. The high duration of ultrasound exposure resulted in structural damage, which was confirmed by scanning electron microscopy. In general, it was revealed that the UOD process prior to freezing was more useful in preventing the quality loss of the samples, as compared to osmodeydration without sonication. These findings, thus indicate that applying UOD is a promising approach for freezing food materials.